Performing science : teaching chemistry, physics and biology through drama - Abrahams, Ian; Braund, Martin (Continuum, 2012)
How to increase students' interest and engagement in science is a challenge shared by teachers around the world. Designing effective science lesson plans using drama and role play requires expertise across two very different subject areas and, as a consequence, many science teachers find it difficult to incorporate this technique into their teaching. This book provides busy teachers with ready-made lesson plans for teaching many abstract scientific principles in a fun and novel way that really engages students. Drawing on and combining the knowledge of biology, chemistry and physics educatio.